Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Associations between individual-level social capital, homophilous and heterophilous social network diversities, and climate stewardship in Japan - Ayako Morita; Nobutoshi Nawa; Douglas Storey; Carol R. Underwood; Pamela J. Surkan; Takeo Fujiwara (Journal of Environmental Management, 2025)

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Insights from a vertebrate model organism on the molecular mechanisms of whole-body dehydration tolerance - Bryan E. Luu; Liam J. Hawkins; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2021)

Short-term neuromuscular, morphological, and architectural responses to eccentric quasi-isometric muscle actions - Dustin J. Oranchuk; André R. Nelson; Adam G. Storey; Shelley N. Diewald; John B. Cronin (European Journal of Applied Physiology, 2021)

Development of fly tolerance to consuming a high-protein diet requires physiological, metabolic and transcriptional changes - Ihor S. Yurkevych; Lindsey J. Gray; Dmytro V. Gospodaryov; Nadia I. Burdylyuk; Kenneth B. Storey; Stephen J. Simpson; Oleh Lushchak (Biogerontology, 2020)

Nonuniform Oxidation Behavior of Loaded Gasoline Particulate Filters - Melanie Moses-DeBusk; John M.E. Storey; Mary A. Eibl; John F. Thomas; Todd J. Toops; Charles E.A. Finney; Josh A. Pihl; Hassina Z. Bilheux; Jens Gregor (Emission Control Science and Technology, 2020)
The results of an experimental study on the oxidation behavior of loaded gasoline particulate filters (GPFs) from a gasoline direct injection (GDI) engine are reported. PM was loaded on uncatalyzed cordierite GPF mini-cores by exposure to exhaust from a light-duty GDI engine operating during a rich acceleration condition on four fuels: 100% gasoline (E0); a 30% blend of ethanol in gasoline (E30); a 24% blend of isobutanol in gasoline (iBu24); or a 48% blend of isobutanol in gasoline (iBu48). The oxidative reactivities of these four types of PM were investigated as a function of temperature. Compared with E0, particulate matter (PM) from the ethanol blend showed a significant shift to lower temperature activity, whereas both isobutanol blends produced PM requiring higher temperatures to achieve complete oxidation. The oxidation kinetics of the E0 and E30 PM were studied in more detail. These cores were used in pulsed-oxidation studies to explore the oxidation kinetics of the PM throughout a stepwise burnout (i.e., regeneration). The results suggest that the reactivity of PM on GPF cores is sensitive to both its environmental history and the type of fuel being used. A unique neutron-imaging study was also performed on E0 and E30-loaded GPF cores to study how the PM layer thicknesses change during a stepwise burnout.

Impacts of Air-Fuel Stratification in ACI Combustion on Particulate Matter and Gaseous Emissions - Melanie Moses-DeBusk; Scott J. Curran; Samuel A. Lewis; R. Maggie Connatser; John M. E. Storey (Emission Control Science and Technology, 2019)

U–Pb isotopic dating of titanite microstructures: potential implications for the chronology and identification of large impact structures - K. Papapavlou; J. R. Darling; D. E. Moser; I. R. Barker; L. F. White; P. C. Lightfoot; C. D. Storey; J. Dunlop (Contributions to Mineralogy and Petrology, 2018)

Histone methylation in the freeze-tolerant wood frog (Rana sylvatica) - Liam J. Hawkins; Kenneth B. Storey (Journal of Comparative Physiology B, 2018)

Phosphorus zoning as a recorder of crystal growth kinetics: application to second-generation olivine in mantle xenoliths from the Cima Volcanic Field - I. Baziotis; P. D. Asimow; T. Ntaflos; J. W. Boyce; F. M. McCubbin; A. Koroneos; D. Perugini; S. Flude; M. Storey; Y. S. Liu; S. Klemme; J. Berndt (Contributions to Mineralogy and Petrology, 2017)

Zircon record of fractionation, hydrous partial melting and thermal gradients at different depths in oceanic crust (ODP Site 735B, South-West Indian Ocean) - A. Pietranik; C. Storey; J. Koepke; S. Lasalle (Contributions to Mineralogy and Petrology, 2017)

Oviposition site selectivity of some New Zealand aquatic macroinvertebrate taxa and implications for stream restoration - R. G. Storey; D. R. Reid; B. J. Smith (New Zealand Journal of Marine and Freshwater Research, 2017)
In many stream restoration projects, macroinvertebrates characteristic of natural conditions do not return despite habitat improvements. One contributing factor may be lack of oviposition sites for some taxa. To understand oviposition requirements of five taxa, we investigated their egg mass distributions on rocks in streams in the Waikato region, New Zealand. We compared insect taxa with aerial adults (caddisfly families Hydrobiosidae and Hydropsychidae, and blackfly species Austrosimulium australense and Austrosimulium sp.) to the fully aquatic limpet Latia neritoides . Egg masses of all taxa were highly aggregated, indicating strong site selection. Hydrobiosidae and both Austrosimulium species preferred ovipositing on emergent rather than submerged rocks. When ovipositing on submerged rocks, Hydropsychidae, Hydrobiosidae and A. australense preferred rocks Latia preferred large rocks (as did all taxa except Austrosimulium sp.) in reaches with low riparian shade. To allow recolonisation and/or persistence of these taxa, restored stream reaches need at least some rocks (or other features) with these characteristics.

Skeletal health and patterns of animal food consumption at S3W1:33 (Tlajinga 33), Teotihuacan - Randolph J. Widmer; Rebecca Storey (Archaeological and Anthropological Sciences, 2017)

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Rheomorphic ignimbrites of the Rogerson Formation, central Snake River plain, USA: record of mid-Miocene rhyolitic explosive eruptions and associated crustal subsidence along the Yellowstone hotspot track - Thomas R. Knott; Marc K. Reichow; Michael J. Branney; David R. Finn; Robert S. Coe; Michael Storey; Bill Bonnichsen (Bulletin of Volcanology, 2016)

Prioritising wetlands subject to secondary salinisation for ongoing management using aquatic invertebrate assemblages: a case study from the Wheatbelt Region of Western Australia - Jessica Delaney; Russell J. Shiel; Andrew W. Storey (Wetlands Ecology and Management, 2016)

Corticosterone levels in feathers and blood of rhinoceros auklets Cerorhinca monocerata are affected by variation in environmental conditions - Amy-Lee Kouwenberg; J. Mark Hipfner; Donald W. McKay; Anne E. Storey (Marine Biology, 2016)

Identification and profiling of miRNAs in the freeze-avoiding gall moth Epiblema scudderiana via next-generation sequencing - Pierre J. Lyons; Nicolas Crapoulet; Kenneth B. Storey; Pier Jr Morin (Molecular and Cellular Biochemistry, 2015)

Transcript expression of the freeze responsive gene fr10 in Rana sylvatica during freezing, anoxia, dehydration, and development - K. J. Sullivan; K. K. Biggar; K. B. Storey (Molecular and Cellular Biochemistry, 2015)

Purification and characterization of a urea sensitive lactate dehydrogenase from the liver of the African clawed frog, Xenopus laevis - Barbara A. Katzenback; Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2014)

Site-specific water quality guidelines: 1. Derivation approaches based on physicochemical, ecotoxicological and ecological data - R. A. van Dam; C. L. Humphrey; A. J. Harford; A. Sinclair; D. R. Jones; S. Davies; A. W. Storey (Environmental Science and Pollution Research, 2014)

QTL involved in the modification of cyanidin compounds in black and red raspberry fruit - J. M. Bushakra; C. Krieger; D. Deng; M. J. Stephens; A. C. Allan; R. Storey; V. V. Symonds; D. Stevenson; T. McGhie; D. Chagné; E. J. Buck; S. E. Gardiner (Theoretical and Applied Genetics, 2013)

An enzymatic bridge between carbohydrate and amino acid metabolism: regulation of glutamate dehydrogenase by reversible phosphorylation in a severe hypoxia-tolerant crayfish - Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2012)

Regulation of tail muscle arginine kinase by reversible phosphorylation in an anoxia-tolerant crayfish - Neal J. Dawson; Kenneth B. Storey (Journal of Comparative Physiology B, 2011)

The regulation of AMPK signaling in a natural state of profound metabolic rate depression - Christopher J. Ramnanan; David C. McMullen; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2010)

Regulation of global protein translation and protein degradation in aerobic dormancy - Christopher J. Ramnanan; Marcus E. Allan; Amy G. Groom; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2009)

The regulation of thapsigargin-sensitive sarcoendoplasmic reticulum Ca2+-ATPase activity in estivation - Christopher J. Ramnanan; Kenneth B. Storey (Journal of Comparative Physiology B, 2008)

A multi‐scale segmentation approach to filling gaps in Landsat ETM+ SLC‐off images - S. K. Maxwell; G. L. Schmidt; J. C. Storey (International Journal of Remote Sensing, 2007)

The Canon of Potato Science - P. C. Struik; W. J. M. Lommen; A. J. Haverkort; R. M. J. Storey (Potato Research, 2007)

The Canon of Potato Science: 44. Damage and Bruising - R. M. J. Storey (Potato Research, 2007)

Divorce in common murres (Uria aalge): relationship to parental quality - Allison T. Moody; Sabina I. Wilhelm; Maureen L. Cameron-MacMillan; Carolyn J. Walsh; Anne E. Storey (Behavioral Ecology and Sociobiology, 2005)

UV-B irradiation stimulates the promoter activity of the high-risk, cutaneous human papillomavirus 5 and 8 in primary keratinocytes - B. Akgl; W. Lemme; R. Garca-Escudero; A. Storey; H. J. Pfister (Archives of Virology, 2005)

Introduced and cryptogenic species in Port Phillip Bay, Victoria, Australia - Ronald E. Thresher; Richard B. Martin; Sue Boyd; Brian F. Cohen; David R. Currie; Martin F. Gomon; Michael J. Keough; John A. Lewis; Matthew M. Lockett; Nicole Mays; Matthew A. McArthur; Tim D. O'Hara; et al. (Marine Biology, 2004)

Freezing survival, body ice content and blood composition of the freeze-tolerant European common lizard, Lacerta vivipara - Voituron Y.; Storey J.; Grenot C.; Storey K. (Journal of Comparative Physiology B, 2002)

Nest-site safety predicts the relative investment made in first and replacement eggs by two long-lived seabirds - Mark J. Hipfner; Anthony J. Gaston; Anne E. Storey (Oecologia, 2001)

Biological, chemical and physical characteristics of downwelling and upwelling zones in the hyporheic zone of a north-temperate stream - Rob J. M. Franken; Richard G. Storey; D. Dudley Williams (Hydrobiologia, 2001)

Reversible phosphorylation control of skeletal muscle pyruvate kinase and phosphofructokinase during estivation in the spadefoot toad, Scaphiopus couchii - Kyra J. Cowan; Kenneth B. Storey (Molecular and Cellular Biochemistry, 1999)

Cyclic AMP-dependent protein kinase: role in anoxia and freezing tolerance of the marine periwinkle Littorina littorea - J. A. MacDonald; K. B. Storey (Marine Biology, 1999)

cAMP-dependent protein kinase from brown adipose tissue: temperature effects on kinetic properties and enzyme role in hibernating ground squirrels - J. A. MacDonald; K. B. Storey (Journal of Comparative Physiology B, 1998)

Antioxidant defenses and lipid peroxidation damage in estivating toads, Scaphiopus couchii - J. E. Grundy; K. B. Storey (Journal of Comparative Physiology B, 1998)

Effects of Seed-Borne Microdochium Nivale on Establishment and Population Density at Harvest of Winter-Sown Oats - J. Humphreys; B. M. Cooke; T. Storey (Cereal Research Communications, 1997)

Suppression of reproductive development and longevity in the redshouldered leaf beetle,Monolepta australis (Col.: Chrysomelidae) by the tachinid,Monoleptophaga caldwelli (Dipt.) - H. A. C. Fay; R. I. Storey; S. G. Defaveri; J. D. Brown (BioControl, 1993)